Design, analysis and fabrication of dish drying rack / Nur Amalia Zahid - Zahid, Nur Amalia (2022)
The theme is about Household Products Technology & Innovation. This project is about to design a dish drying rack become an auto drying dish rack that useful for household work. Since nowadays, lot of people are busy with their works, and everything need to be rush and punctual. So, with this auto dish drying rack, it can save their time to organized and do not need to dry the dishes manually again. It has been very useful since the first invented in 1876 [1], where the dishes stand up and drip dry without getting water spots. The cutlery all organized in one section after washed all the dishes and then it is up to the air to do the rest of the work which is the drying process. However, there are still some problems that need to be fixed to get the full satisfactions from the user. Various methods such as collecting data from the survey, concept design, and fabrication idea were planned to get more improvement and innovation that they needed.